PENGARUH DEMOKRASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Imahda Khoiri Furqon; Mryn, Maryani (Perwira Journal of Economics & Business, 2024)
This study aims to determine the influence of democracy on economic growth in Indonesia within three years, namely 2020-2022. This study uses a quantitative approach with secondary data taken from the website of the Badan Pusat Statistik (BPS) Indonesia with democratic variables represented with data on aspects of civil liberties, aspects of political rights and aspects of democratic institutions as independent variables and economic growth as the following variables. The result of this study is that democracy simultaneously has a significant effect on economic growth in Indonesia, but the strength of influence is very weak at 11,89%. Partially, aspects of civil liberties have a significant effect on economic growth, but aspects of political rights and aspects of democratic institutions do not have a significant effect on economic growth in Indonesia.